Belief in god based on the national philosophy of education amongst Malaysian secondary school teachers - Ismail, Habsah; Md. Yunus, Aida Suraya; Wan Ali, Wan Zah; Hamzah, Ramlah; Abu, Rosini; Nawawi, Hapsah (Eurojournals, 2009)
The National Philosophy of Education (NPE) formulated in the year 1987 is the most important document that guides and reinforces the direction and goal of education in Malaysia. With the “belief and devotion to God” as its main principle belief, this document directs the goals and mission towards accomplishing the educational aim of the country, that is,” to produce individuals who are intellectually, spiritually, emotionally and physically balanced and harmonious, based on a firm belief in and devotion to God.” This paper seeks to discuss the findings of a study conducted on twelve Malaysian secondary school on their belief and devotion to God based on the NPE. This qualitative study uses the interview method to solicit the teachers’ belief and devotion to God. The findings show that the belief is accepted by the teachers although they are faced with several constraints in fully implementing it in their teaching.